The Optimizing of Rahn Service for The Development of Islamic Banking in Indonesia - Lidia Rahmah Maulidia (Jurnal Iqtisad, 2003)
This paper considers rahn in classical fiqh with various opinions from Islamic schools of jurisprudence (madzhab). Here, one issue becoming debate among Moslem scholars is the use of mortgaged objects. Rahn is adopted by Islamic banking and becomes one of its services offered to the market. In practice, rahn appears as two different products. First, as a complementary product, that is additional transaction (guarantee/collateral) for other products such as ba’i al-murabahah financing. In this case, Islamic banks can detain debt-ors’ mortgaged objects because of transaction. Second, as an independent product. In some Moslem countries including Malaysia, rahn has been being used as an alternative for the conventional pawnshop. Differing from that in conventional, in rahn debtors are not charged with interest. Instead, they are obliged to pay entrustment cost, conservancy cost, and custody cost, as well as appraisal cost. The main difference between such rahn costs and interest is, whereas interest can accumulate, costs of rahn can be paid once and speci-fied in advance.People interest toward conventional pawn service is exactly high because they had to get cash. This can be seen from the increase of pawnshop turnover from year to year. Rahn service is thus potential to be implemented and maximized. Logically, charged with high interest people still considering pawnshop as benefactor, much less Islamic banking with rahn service charging no interest. Hence, we are natural to optimistically introduce rahn service. Of course with manners and regulations that are free from the elements of riba.